Impact of earthquake on river water quality based on combination of satellite data and groundwater analysis - K. Jafarpour; K. Leangkim; Aznah N. Anuar; Ali M. Yuzir; Faizah C. Ros; Nur F. Said; Jun Asanuma (Watershed Ecology and the Environment)
The impact of an earthquake on river water quality is massive, and the quality of life and environment typically changes as a result of a quick drop in the environment system. A 6.0 magnitude earthquake struck the Ranau area of Sabah, Malaysia, in 2015, affecting the Liwagu River’s water quality. Satellite data on earthquakes, coupled with local water quality data collecting, allows for an accurate assessment of water quality parameters. As a result, the Sabah Water Department provided secondary water quality data from Bambangan and Kimolohing on the Liwagu River. Following that, turbidity, color, pH, electric conductivity (EC), total dissolved solids (TDS), dissolved oxygen (DO), nitrate (NO3−), iron (Fe), manganese (Mn), aluminum (Al), alkalinity, hardness, chloride (Cl-), and sulfate (SO42−) were chosen. The investigation discovered unusually high turbidity and color in the water on June 17, 2015, as well as elevated levels of Al, Fe, and Mn. DO concentrations plummeted to 3.8 mg/L on the same day. Statistical analyses, employing the Kruskal-Wallis test, identified significant parameters—Fe (0.001) and Mn (0.001) at both stations, turbidity (0.001), and color (0.003) in Kimolohing, and Al (0.027) in Bambangan. Recovery in water quality took two weeks to two months, with iron and manganese requiring over six months for restoration. The earthquake didn’t solely dominate the impact but altered pollution sources to the river. The discussion highlights the synthesis of spatial and temporal dynamics enabled by the integration of ground and satellite data. This approach not only refines retrospective analyses but also propels us into predictive modeling, enhancing preparedness for future seismic events. The study’s holistic environmental impact assessment extends beyond water quality, unraveling cascading effects on ecosystems, soil, and vegetation. Informed decision-making for sustainable resource utilization emerges as a pivotal outcome, emphasizing the interconnectedness of seismic activity, rainfall patterns, and water quality. The study serves as a blueprint for future environmental assessments, emphasizing multifaceted approaches to understand and mitigate the complex impacts of seismic events on water resources.